2017
DOI: 10.1002/iub.1618
|View full text |Cite
|
Sign up to set email alerts
|

Copper metallothioneins

Abstract: Metallothioneins (MTs) are a class of low molecular weight and cysteine-rich metal binding proteins present in all the branches of the tree of life. MTs efficiently bind with high affinity several essential and toxic divalent and monovalent transition metals by forming characteristic polynuclear metalthiolate clusters within their structure. MTs fulfil multiple biological functions related to their metal binding properties, with essential roles in both Zn(II) and Cu(I) homeostasis as well as metal detoxificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 71 publications
1
84
0
1
Order By: Relevance
“…A similar conclusion has been drawn from computational studies in which, in the absence of metallochaperons, the local metal concentrations were found critical for the metal specificity of proteins [37]. Although the enhanced copper-thionein character of MT-3 over MT-1/-2 may still, in part, reflect subtle differences between the two sequences and consequently their structural properties [38], it would appear that the reported metal binding preference of various MTs in E. coli cultures may not exactly reflect the buffered metal concentrations present in different mammalian cell types where the MT biosynthesis occurs.…”
Section: Structural and Chemical Properties Of Metallothionein-3supporting
confidence: 62%
“…A similar conclusion has been drawn from computational studies in which, in the absence of metallochaperons, the local metal concentrations were found critical for the metal specificity of proteins [37]. Although the enhanced copper-thionein character of MT-3 over MT-1/-2 may still, in part, reflect subtle differences between the two sequences and consequently their structural properties [38], it would appear that the reported metal binding preference of various MTs in E. coli cultures may not exactly reflect the buffered metal concentrations present in different mammalian cell types where the MT biosynthesis occurs.…”
Section: Structural and Chemical Properties Of Metallothionein-3supporting
confidence: 62%
“…Cells were spun down and resuspended in 100 mL of LB with 100 µg/mL carbenicillin. Optical density at 600 nm (OD 600nm ) was monitored each hour after resuspension until OD 600nm reached between 0.6 and 0.8, then OD 600nm was measured at 24 h, 48 h and 72 h. It has been shown that MT expression was induced and upregulated when microorganisms are under heavy metal stress [5,6,17,18]. To further investigate whether the expression of C. albicans MT in E. coli impact the bacterial tolerance to heavy metal, we cultivated the bacteria in the presence of 0.2 mM CuSO 4 .…”
Section: Monitoring Cell Growthmentioning
confidence: 99%
“…In particular, there is an increasing interest in the exploitation of the cysteine-rich metal-binding proteins, metallothioneins (MTs), in the development of biofactories for metal NP production. MTs are found in all eukaryotes, as well as some prokaryotes, and play an important role in intracellular metal distribution, accumulation, as well as protection of cells against heavy metal toxicity and oxidative stress [5,6]. The Cys-Xaa-Cys clusters of MTs can act as a reducing functional group for the reduction of metal ions, chelation, and accumulation of metal particles in the cells [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations